Redox modulation of vitagenes via plant polyphenols and vitamin D: Novel insights for chemoprevention and therapeutic interventions based on organoid technology. (October 2021) - Scuto, Maria; Trovato Salinaro, Angela; Caligiuri, Isabella; Ontario, Maria Laura; Greco, Valentina; Sciuto, Nello; Crea, Roberto; Calabrese, Edward J.; Rizzolio, Flavio; Canzonieri, Vincenzo; Calabrese, Vittorio
Highlights: Dietary polyphenols are promising chemotherapeutic agents that can modulate oxidative stress. Polyphenols and Hidrox in particular, as a small molecule, can reverse ROS production and inflammation by activating Nrf2 nuclear translocation and transcription of vitagenes. Organoid technology represents an excellent model to develop novel personalized therapies and predictive drug testing before clinical therapeutic application. Abstract: Polyphenols are chemopreventive through the induction of nuclear factor erythroid 2 related factor 2 (Nrf2)-mediated proteins and anti-inflammatory pathways. These pathways, encoding cytoprotective vitagenes, include heat shock proteins, such as heat shock protein 70 (Hsp70) and heme oxygenase-1 (HO-1), as well as glutathione redox system to protect against cancer initiation and progression. Phytochemicals exhibit biphasic dose responses on cancer cells, activating at low dose, signaling pathways resulting in upregulation of vitagenes, as in the case of the Nrf2 pathway upregulated by hydroxytyrosol (HT) or curcumin and NAD/NADH-sirtuin-1 activated by resveratrol. Here, the importance of vitagenes in redox stress response and autophagy mechanisms, as well as the potential use of dietary antioxidants in the prevention and treatment of multiple types of cancer are discussed. We also discuss the possible relationship between SARS-CoV-2, inflammation and cancer, exploiting innovative therapeutic approaches with HT-rich aqueous olive pulp extract (Hidrox®), a natural polyphenolic formulation, as well as the rationale of Vitamin D supplementation. Finally, we describe innovative approaches with organoids technology to study human carcinogenesis in preclinical models from basic cancer research to clinical practice, suggesting patient-derived organoids as an innovative tool to test drug toxicity and drive personalized therapy.